From itinerant teachers to adult educators: Joan Carles I Adult School - González Rodríguez, Juan Agustín; Bernad Cavero, Olga (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article seeks the recognition of the work of adult educators and their struggles from the end of the dictatorship to the present to establish the foundations of adult education. With a qualitative exploratory methodology, based on in-depth interviews with the professionals who were involved, this article describes the origins, the difficulties and the processes carried out in the creation and official recognition of the Joan Carles I adult education center, located in the La Mariola neighborhood of Lleida, which has its own idiosyncrasy.